Inuit Language Protection Act
Inuit Language Protection Act is the only Act in Canada that aims to protect and revitalize a first peoples’ language. It came into force in 2008 and established the Ministry of Languages. The objective of the Act is to increase the population of Inuit who can speak and read their language fluently and to help Nunavummiut achieve this goal.